Temsirolimus Maintenance Therapy After Docetaxel Induction in Castration-Resistant Prostate Cancer. (5th November 2015) - Emmenegger, Urban; Booth, Christopher M.; Berry, Scott; Sridhar, Srikala S.; Winquist, Eric; Bandali, Nesan; Chow, Annabelle; Lee, Christina; Xu, Ping; Man, Shan; Kerbel, Robert S.; Ko, Yoo-Joung
Abstract: Lessons Learned : Temsirolimus maintenance therapy after docetaxel induction chemotherapy is safe in patients with castration-resistant prostate cancer, although biochemical or tumor responses are rare; does not diminish quality of life; and delays radiological and/or symptomatic progression by approximately 6 months. Background: No standard therapy is available for men with castration-resistant prostate cancer (CRPC) who have responded to docetaxel and do not yet have disease progression. Hence, we designed a single-arm phase II trial to explore whether the mTOR inhibitor temsirolimus can maintain the response to docetaxel without compromising quality of life. Methods: After successful docetaxel induction (75 mg/m 2 every 3 weeks; 6–10 cycles), 21 CRPC patients underwent temsirolimus maintenance treatment (25 mg weekly; 4 weeks per cycle). The primary endpoint was the time to treatment failure (TTTF) (i.e., radiological and/or symptomatic progression). The secondary endpoints included the tumor response rate (RECIST 1.0), safety (National Cancer Institute Common Terminology Criteria for Adverse Events, version 3.0), quality of life (Functional Assessment of Cancer Therapy-Prostate [FACT-P]), pain (Present Pain Intensity [PPI] scale), prostate-specific antigen (PSA) parameters, including time to PSA progression (TTPP) according to Prostate Cancer Clinical Trials Working Group criteria, and serial enumeration of circulating endothelial cells (CECs) and endothelial progenitor cells (CEPs). Results: Patients received a median of 7 cycles of temsirolimus (range, 1–28), resulting in a median TTTF of 24.3 weeks (95% confidence interval [CI], 16.1–33.0), 1 partial tumor response (4.8%), 1 PSA response (4.8%), and a median TTPP of 12.2 weeks (95% CI, 7.8–23.9). Grade 3-4 adverse events were infrequent, and FACT-P and PPI scores remained stable during treatment. CECs did not predict clinical benefit, and CEPs were not consistently detectable. Conclusion: Temsirolimus maintenance therapy after successful docetaxel induction is feasible, does not adversely affect quality of life, and, in this exploratory single-arm phase II study, resulted in a median TTTF of 24.3 weeks.